Law and Ethics in Nursing and Healthcare : An Introduction - Avery, Graham, 1954- (2017)
A concise, highly accessible introduction to the key legal requirements needed to practice professionally within nursing and healthcare - a core element of the undergraduate nursing and healthcare curriculum. Each chapter supports theoretical learning with learning objectives, legislative case examples and practical scenarios.
Previous edition: 2013.
Includes bibliographical references and index.
Keywords: Nursing -- Law and legislation -- England; Nursing -- Law and legislation -- Wales; Nursing ethics -- England; Nursing ethics -- Wales; Law